Study of improvement upon cork stoppers washing - Branco, Diana Andreia Gomes (2024)
Cork is the outer bark extracted from the cork oak tree (Quercus suber L.) and is widely used in different materials due to its unique physical properties. Wine stoppers occupy the largest cork market segment with about 72%, where the natural cork stoppers have a distinct position with 56% of the total cork stoppers production. The main challenges in the area consist in finding ways to improve the performance of stoppers in winemaking applications and adjacent food areas. A better understanding of the fundamental aspects of cork chemical composition and structural features of its main components within the context of their behavior in cork processing is another research point to consider. Reactive washing (RW) is the main industrial process responsible for the disinfection, appearance and functional performance of stoppers. The main objective of this thesis, carried out at the University of Aveiro in collaboration with the Amorim Cork, S.A., was to study reactive washing (RW) process of natural cork stoppers in order to achieve their better appearance, color uniformity and technical performance. Special attention was given to the structural characteristics of the macromolecular components of natural cork stoppers and their surface response to RW. Accordingly, the isolated cork components were evaluated by wet chemistry methods, GC-MS, FTIR and 1D/2DNMR spectroscopy and X-ray scattering diffraction. The natural cork stopper morphology was studied by SEM and the surface chemistry by UV-vis DR, FTIR-ATR and confocal Raman spectroscopy. Surface properties were assessed by 3D optical profilometry and contact angle measurements. The optical properties were evaluated by ISO brightness and CIElab color parameters. The refinement of the chemical composition and structural characteristics of the main macromolecular components of natural cork stoppers (suberin, lignin, cellulose and xylan) were carried out and related to their surface properties. The anisotropy in the surface properties and the roughness of the top and lateral of natural cork stoppers was explained by the difference in the exposure of the phellogen cell wall layers and as a result of mechanical damage that occurred during the stopper production. The differences in the surface chemical composition and topology explain the higher polarity index of the top surface that predetermines it better wettability with water and hydroalcoholic solutions than the lateral surface of the stopper. . Reactive washing (RW), being an aggressive treatment with hydrogen peroxide under strong alkaline conditions, impairs the surface properties of cork stoppers regarding their wettability, which is due to the significant degradation of suberin on the cork surface. The surface degradation in RW deteriorates further processing of cork stoppers and their functional performance. The optimization of the conventional reactive washing with H2O2, the implementation of ozone as a bleaching agent for the natural cork stoppers and the combination of ozone treatment and optimized conventional reactive washing with H2O2 were proposed to improve the economic feasibility and the quality performance of cork stoppers. The optimization of the conventional reactive washing and the ozone treatment were accomplished using a three fractional factorial design and response surface methodology (RSM). The process variables conditions that maximize the effect of ozone on the stopper were chosen using statistical methods (ANOVA, Tukey test, and paired samples T-test). The results revealed that two variables of conventional RW (H2O2 and NaOH concentrations) have a greater effect on the response than the others (e.g. reaction time and volume of washing water). By applying numerical model optimization with an ISO brightness target (ca. 34 %ISO), it was possible to achieve a significant improvement in terms of reagent savings, with a reduction of 37% for H2O2, and 33% for NaOH and washing water, respectively. The introduction of ozone as RW reagent allowed the increase of ca. 5% ISO brightness of natural cork stoppers within 15 min with minimal degradation of their surface. The combination of a first RW stage with ozone and a second stage of optimized conventional reactive washing with H2O2 allowed the further reduction of hydrogen peroxide consumption, oxidation time and washing water volume, while maintaining the final natural stopper brightness and functional performance. This optimized RW processes (with and without ozone treatment) revealed better preservation of the stopper surface from suberin degradation with controlled wettability and improved performance towards functional coating with paraffin and silicone. At last, the basic quality parameters (pH, humidity, residual content of hydrogen peroxide, dust content, color migration, capillarity progression and absorption of wine by the stoppers) commonly used in the industry were evaluated for the cork stoppers from the different reactive washing processes. Similar results were obtained when comparing these quality parameters of the optimized RW with the conventional one, with lower consumption of reagents, less process time and better functional performance of stoppers.